Marked effects of novel selective peroxisome proliferator-activated receptor α modulator, pemafibrate in severe hypertriglyceridemia: preliminary report - Iitake, Chie (Cardiovasc Diabetol, 2020)
BACKGROUND: Currently available treatments have only been partly successful in patients with severe hypertriglyceridemia, including those with high serum triglycerides above 1,000 mg/dL (11.3 mmol/L), who often suffer from acute pancreatitis. Pemafibrate is a novel selective peroxisome proliferator-activated receptor α modulator (SPPARMα) which has been developed as an affordable oral tablet in Japan. We herein report the first three patients with severe hypertriglyceridemia who were successfully treated with pemafibrate. METHODS: Three patients with fasting serum triglyceride (TG) levels above 1,000 mg/dL (11.3 mmol/L) were treated with pemafibrate (0.2–0.4 mg/day, 0.1–0.2 mg BID). RESULTS: Serum TGs decreased from 2,000–3,000 mg/dL (22.6–33.9 mmol/L) to < 250 mg/dL (2.8 mmol/L) without adverse effects in all three patients. Serum TGs in Patient 1 and 2 decreased from 1,326 mg/dL (15.0 mmol/L) to 164 mg/dL (1.9 mmol/L) and from 2,040 mg/dL (23.1 mmol/L) to 234 mg/dL (2.6 mmol/L), respectively. Patient 3 with type 2 diabetes and 12.1% (109 mmol/mol) hemoglobin A1c had a TG level of 2,300 mg/dL (26.0 mmol/L). Even after glycemic control improved, TG remained high. After pemafibrate administration, TG decreased to 200 mg/dL (2.3 mmol/L). All patients showed no serious adverse events. CONCLUSIONS: Pemafibrate demonstrated potential efficacy and safety for severe hypertriglyceridemia which may contribute to the prevention of acute pancreatitis, in a manner that can be easily prescribed and used as an oral tablet.